Adjectives in Heritage Spanish - Liliana Sánchez (Universitat Autònoma de Barcelona, 2021)
Ordering of predicative adjectives within the Noun Phrase varies cross linguistically in systematic ways (Cinque 2010). In Spanish adjectival ordering exhibits more flexibility than in English. To test the extent to which the stricter word order in English affects Spanish adjectival ordering, 35 heritage bilingual Spanish speakers living in an English dominant environment were asked to judge adjectival word orders and interpret adjective elisions.  Results indicate acceptance of adjectival ordering involving roll up movement (Cinque 2010), not possible in English. They also show the ability to interpret elisions in contexts involving the same type of movement. These results provide evidence for the availability of flexible ordering in Spanish even among Spanish-English bilinguals.